Senja Coffee Coffee Shop Business Plan In Sentul - Vita Putri Saraswati; Suwandi, Suwandi (Jurnal Scientia, 2024)
The development of coffee shops in the modern era is currently growing, it is proof that people who behave consumptively as coffee connoisseurs are increasing. Senja Coffee Sentul is located in the highlands of Sentul, using a 50:50 mixture of Robusta and Arabica coffee so that the sweet, sour, bitter taste of the original coffee beans produced will be balanced/balanced and delicious. SCS has a Romantic-Ethnic concept as a place with beautiful, simple, clean, comfortable, but romantic views at affordable prices for young people, or families with an attractive layout and interior, which consists of Indoor (there is a special romantic table spot) and outdoor with beautiful open spaces. Payment methods are not only in cash but can also be non-cash through an EDC machine for debit/credit cards, or with a QR Code that is connected to supporting applications such as Gopay, OVO, Shopeepay, Travelokapay and mobile banking. The method used in this research is a qualitative descriptive analysis based on information obtained from the literature study and the applied business model, with the Business Model Canvas instrument. The assessment of Senja Coffee Sentul's business plan is carried out with NPV analysis parameters with positive results, Payback Period of 0.9 or for 10 months with an IRR of 69%, which means that SCS is feasible to run.